Integrating Health Education, Postural Screening, and Plyometric Exercise to Improve Adolescent Physical Fitness - Rijal Rijal; Yusfina Yusfina; Irianto Irianto; Melda Putri; Andi Rahmaniar Suciani Pujiningrum; Salki Sadmita; Immanuel Maulang (Jurnal Abmas Negeri (JAGRI), 2026)
This community service program addressed increasing adolescent health issues, including poor posture habits, low physical activity participation, and declining physical fitness. The program aimed to prevent postural disorders and improve physical fitness among students at SMA Negeri 21 Makassar through health education, posture and fitness screening, and plyometric exercise training. Eighty-seven students participated in educational sessions on the importance of physical activity and proper posture, screening of anthropometric characteristics, handgrip strength, dynamic balance, and postural alignment, and 37 students participated in plyometric exercises. Screening data were analyzed descriptively. The data showed that most students had body weight predominantly ranging from 40.1–50 kg and height from 151–160 cm, 19 students demonstrated lower grip strength, and the Y Balance Test indicated good dynamic balance ability, with left–right differences below 10%, suggesting a low risk of injury. Mild postural deviations, including forward head posture and rounded shoulders, were identified in several students. The study generated baseline data regarding students’ posture and fitness conditions, which could support future physical education programs. This study also provided health education and independent plyometric exercise training for students. This activity contributed to the strengthened promotive and preventive collaboration among physiotherapists, teachers, and schools in supporting adolescent physical health.